Antibacterial non-woven nanofibers of curcumin acrylate oligomers - Killi, Naresh; Paul, Vejendla Luke; Gundloori, Rathna Venkata Naga (New Journal of Chemistry, 2015)
Two new (meth) acrylate monomers, namely, 4-((1E,6E)-7-(4'-hydroxy-3-methoxyphenyl)-3,5-dioxohepta-1,6-dienyl)-2-m ethoxyphenyl acrylate or curcumin monoacrylate (CmA) and 4-((1E, 6E)-7-(4'-hydroxy-3-methoxyphenyl)- 3,5-dioxohepta-1,6-dienyl)-2-methoxyphenyl methacrylate or curcumin monomethacrylate (CmMA), are synthesized by reacting (1E, 6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-dione (curcumin) with acryloyl chloride and methacryloyl chloride, respectively. The respective derivatives are polymerized by free radical polymerization using an initiator, 2,2-azobisisobutyrontrile (AIBN), to obtain the oligomer of curcumin monoacrylate (OCM) and the oligomer of curcumin monomethacrylate (OCMA). The oligomers are characterized by FTIR, H-1 NMR and UV-vis spectroscopy. The molecular weights of the oligomers are determined by GPC to range between 2000 and 5500 Da. The melting temperature (T-m) and degradation temperature of the respective oligomers are evaluated by thermal analysis. The melting temperature of the oligomers ranged from 195 to 197 degrees C. Antibacterial studies are evaluated against Staphylococcus aureus, in which the minimum inhibitory concentration (MIC) of OCA1 is 27 mg mL(-1). The blends of the individual oligomers with poly(lactic acid) are electrospun to obtain the respective non-woven nanofiber mats. Nanofibers are formed, with the diameter ranging from 400 to 750 nm, and the nanofiber mats are porous. Because the nanofiber mats are antibacterial and highly porous, they may have potential application as a wound dressing material for tissue regeneration.

Design and fabrication of mechanically strong nano-matrices of linseed oil based polyesteramide blends - Killi, Naresh; Dhakare, Runali Arjun; Singam, Amarnath; Lokanadham, Metta; Chitikeshi, Harshavardhan; Gundloori, Rathna Venkata Naga (Medchemcomm, 2016)
New nanomaterials of bio-origin with improved mechanical properties are in demand for biomedical application. Therefore, we propose to design and fabricate bioactive nano-matrices with good mechanical strength using polyesteramides derived from linseed oil. Polyesteramide was synthesized from linseed oil and blended with poly(L-lactide) and human serum albumin to enhance the mechanical strength, biodegradation, biocompatibility and hydrophilicity. The various blend solutions with and without drugs (triclosan and metronidazole) were electrospun into non-woven nano-matrices. The morphology of the nano-matrices represented smooth and fine nanofibers with the diameter ranging from 300 to 400 nm. Drug binding efficiency, cytotoxicity, hydrophilicity, thermal and mechanical studies indicated their suitability as biomaterials. To demonstrate their utility, the drug release kinetics and antibacterial properties were evaluated. The metronidazole loaded nano-matrices showed drug release up to 8 h, beyond which no release was observed until 72 h. Antibacterial studies were done using the drugs triclosan and metronidazole. The antibacterial activity of the drug loaded nanofiber mats increased with the increase in drug concentration. The uniqueness of the developed nano-matrices of polyesteramide blends is that their mechanical strength is 3-fold higher than that of the nano-matrices of poly(L-lactide), which is one of the essential features of these nano-matrices to be used as a biomaterial for biomedical applications.

Proteins as nanocarriers to regulate parenteral delivery of tramadol - Agrawal, Shubhang; Patel, Pratikshkumar R.; Gundloori, Rathna Venkata Naga (ACS Omega, 2019)
Tramadol (Td) is a centrally acting opioid analgesic drug used for the treatment of moderate to severe pain. However, the half-life of Td is about 6-8 h, which is a major drawback. To increase the half-life of Td, it needs to be entrapped in a suitable substrate with the capability to release the drug for an extended period of time. Accordingly, in our studies, new protein blends in various compositions were prepared using hydrophilic (egg albumin) and hydrophobic (zein) proteins and fabricated them as nanoparticles with Td by the desolvation method. The prepared nanoparticles were characterized using analytical techniques. The morphology and diameter of the nanoparticles were determined by an environmental scanning electron microscope. The interactions between Td and proteins were confirmed by fluorescence spectroscopy, and the secondary structural changes were evaluated by circular dichroism. The hemolysis test and MTT assay indicated that the nanoparticles were nontoxic, and drug release studies showed an extended duration of release of Td for more than 48 h. The mechanism of the drug release followed the zero order. The overall studies inferred that these protein based nanoparticles have potential to release Td at a slow rate for an extended period of time. Further manipulation of the protein composition may regulate the duration of Td release for an effective therapy.

Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions - Patel, Pratikshkumar R.; Pandey, Komal; Killi, Naresh; Gundloori, Rathna Venkata Naga (Polymer Engineering and Science, 2021)
A hybrid of poly-l-lactic acid (PLA) and poly-epsilon-caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45 degrees with the increase in EA concentration. The rate and extent of swelling was increased 3-folds with the addition of EA. Release studies of NM showed maximum amount of MTz was released with the increase in MTz concentration (>85%). The MTz interaction with EA and structure stability of EA was confirmed from fluorescence and circular dichroism studies. NM showed increase in inhibition of bacterial growth of Staphylococcus aureus and Escherichia coli with the increase in MTz concentration. Cell viability of the NM was >80% and also, the cell proliferation increased as EA content increased. NM hemolytic activity was less than 5% suggesting compatibility. Hence, results concluded that EA had regulated hydrophobicity, promoted cell interactions, and proliferation and therefore, NM is considered safe for tissue regeneration.
Keywords: Biocompatibility; Biomaterials; drug delivery systems; egg albumin; electrospinning; nanofibers; polyesters

One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization

Bioinspired hyaluronic acid based nanofibers immobilized with 3, 4-difluorobenzylidene curcumin for treating bacterial infections - Patel, Pratikshkumar R.; Singam, Amarnath; Iyer, Arun K.; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Curcumin (Cur) is a natural polyphenol with multifaceted pharmacological functions, exploited extensively for biomedical applications. Traditionally curcumin is being used as an antimicrobial agent. However, to improvise the pharmacological properties, it is being modified synthetically. One of such modified Cur is 3, 4- difluorobenzylidene curcumin (CDF) which is aimed for enhancing the anti-cancer properties. Though there are reports on the studies of anti-cancer properties involving CDF, the anti-bacterial property is yet to be demonstrated. Accordingly, in our studies, we prepared bioinspired hyaluronic acid blends immobilized with CDF and fabricated non-woven nanofiber mats. These nanofiber mats were characterized and demonstrated in vitro cell culture studies, which involved cell viability, hemolysis, anti-bacterial and cell scratch assay to understand their efficacy in treating bacteria. The molecular docking studies of CDF and Cur were performed on the dihydrofolate reductase (DHFR) enzyme receptor, which is an essential protein of S.auerus (Staphylococcus aureus). The results of MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay, and hemolysis of the respective nanofiber mats with Cur and CDF showed non-toxicity and were compatible with blood cells. Further, the cell proliferation and adherence recorded >60% fibroblast cells for the nanofiber mats. The anti-bacterial property of Cur and CDF was similar. The in vitro release studies for the respective Cur and CDF loaded nanofiber mats recorded a release of 25 and 37%, respectively. From these studies, we concluded that the CDF sustained its antibacterial property in addition to the improved anti-cancer property; hence CDF being synergetic, it will have a better scope in cancer therapy.
Keywords: anti-bacterial; curcumin; nanofibers; tissue engineering; wound Healing

Blend of neem oil based polyesteramide as magnetic nanofiber mat for efficient cancer therapy - Patel, Pratikshkumar R.; Singam, Amarnath; Dadwal, Arun; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Stearic acid-coated magnetic nanoparticles (SMN) and FU (5-Fluorouracil) were immobilized in the blends of neem oil-based polyesteramide and fabricated as nanofiber mat (NM) for controlled release of FU under the influence of an external magnetic field for targeted drug delivery to treat cancer efficiently. Analyzed the surface morphology of the fibers using E-SEM, it was observed that the fibers were smooth with the diameter ranging from 250 to 450 nm. TEM studies showed the uniform distribution of SMN in the nanofibers. The physico-chemical properties of NM and raw materials were analyzed using FTIR, TGA, and XRD. The results suggested that the polymers were well blended. In-vitro FU release studies of the NMs recorded a significant difference in the cumulative percentage of FU release from SMN-NMs. The SMN-NMs released 95% of FU in 4 h, whereas, NMs released 83% of FU in 24 h. The cell viability assay for the NM was evaluated in the L929 mouse fibroblast cells, where >75% of cells were viable. The hemolysis assay for the developed SMN-NF showed <5% of hemolysis, which indicated the NMs were safe for application. The anti-cancer activity of FU loaded SMN-NF was analyzed in the MCF-7 cancer cell line, which recorded more than 50% cell death within 24 h. From SQUID analysis, we found that the 10% SMN were superparamagnetic in nature, the magnetization at 30 kOe was observed to be 4.3 emu/g. Based on the in vitro results, we concluded that the developed SMN-NMs are recommended for in vivo studies to understand their efficacy for the targeted drug delivery to treat cancer.
Keywords: 5-Fluorouracil; drug release; electrospinning; Magnetic nanoparticles; nanofibers; Stearic acid

Review on electrospun nanofibers for multiple biomedical applications - Patel, Pratikshkumar R.; Gundloori, Rathna Venkata Naga (Polymers for Advanced Technologies, 2023)
Electrospinning is a well-known technique since 1544 to fabricate nanofibers using different materials like polymers, metals oxides, proteins, and many more. In recent years, electrospinning has become the most popular technique for manufacturing nanofibers due to its ease of use and economic viability. Nanofibers have remarkable properties like high surface-to-volume ratio, variable pore size distribution (10-100 nm), high porosity, low density, and are suitable for surface functionalization. Therefore, electrospun nanofibers have been utilized for numerous applications in the pharmaceutical and biomedical field like tissue engineering, scaffolds, grafts, drug delivery, and so on. In this review article, we will be focusing on the versatility, current scenario, and future endeavors of electrospun nanofibers for various biomedical applications. This review discusses the properties of nanofibers, the background of the electrospinning technique, and its emergence in chronological order. It also covers the various types of electrospinning methods and their mechanism, further elaborating the factors affecting the properties of nanofibers, and applications in tissue engineering, drug delivery, nanofibers as biosensor, skin cancer treatment, and magnetic nanofibers.
Keywords: biomaterial; drug delivery; electrospinning; Nanofiber; tissue engineering